The Effects of the COVID-19 Pandemic on the Diagnosis and Follow-up of Osteoporosis - Gülseren Demir Karakılıç; Ferda Surel; Esra Şahingöz Bakırcı (Düzce Tıp Fakültesi Dergisi)
Aim: The coronavirus disease 2019 (COVID-19) pandemic has impacted the follow-up and treatment processes of many chronic diseases, including osteoporosis. This study aimed to determine whether 25-hydroxyvitamin D (25(OH)D) levels and bone mineral density (BMD) measurements in patients diagnosed with osteoporosis were affected during the COVID-19 pandemic to assess changes in follow-up and treatment protocols.Material and Methods: The study included 598 patients diagnosed with osteoporosis between December 1, 2018, and March 1, 2020. The duration of follow-up after the pandemic, femoral neck T-score and BMD value, lumbar vertebrae total (L1-4) T-score and BMD value, 25(OH)D levels, and medical treatments for osteoporosis were recorded retrospectively.Results: The mean duration of follow-up visits after the pandemic was nearly two years. 25(OH)D levels were significantly higher in the post-pandemic period than in the pre-pandemic period (p